Controllability results for fractional integrodifferential systems in Banach spaces. (1st January 2014) - Radhakrishnan, Bheeman; Balachandran, Krishnan; Anukokila, Paraman
In this paper, we study the controllability of fractional non-linear evolution integrodifferential system in Banach spaces. Further quasilinear and neutral evolution systems are discussed. The results are obtained by using fractional calculus and a fixed point principle.